Biodiesel technology and applications - Inamuddin, 1980-; Ahamed, Mohd Imran; Boddula, Rajender; Rezakazemi, Mashallah (Scrivener ; Wiley, 2021)
Energy technologies have attracted great attention due to the fast development of sustainable energy. Biodiesel technologies have been identified as the sustainable route through which overdependence on fossil fuels can be reduced. Biodiesel has played a key role in handling the growing challenge of a global climate change policy. Biodiesel is defined as the monoalkyl esters of vegetable oils or animal fats. Biodiesel is a cost-effective, renewable, and sustainable fuel that can be made from vegetable oils and animal fats. Compared to petroleum-based diesel, biodiesel would offer a non-toxicity, biodegradability, improved air quality and positive impact on the environment, energy security, safe-to-handle, store and transport and so on. Biodiesels have been used as a replacement of petroleum diesel in transport vehicles, heavy-duty trucks, locomotives, heat oils, hydrogen production, electricity generators, agriculture, mining, construction, and forestry equipment. This book describes a comprehensive overview, covering a broad range of topics on biodiesel technologies and allied applications. Chapters cover history, properties, resources, fabrication methods, parameters, formulations, reactors, catalysis, transformations, analysis, in situ spectroscopies, key issues and applications of biodiesel technology. It also includes biodiesel methods, extraction strategies, biowaste utilization, oleochemical resources, non-edible feedstocks, heterogeneous catalysts, patents, and case-studies. Progress, challenges, future directions, and state-of-the-art biodiesel commercial technologies are discussed in detail. This book is an invaluable resource guide for professionals, faculty, students, chemical engineers, biotechnologists, and environmentalists in these research and development areas.